Analisis Kualitas Website Dukcapil Kabupaten Sorong Selatan Menggunakan Metode WebQual 4.0 - Jordi Ambrosius Tipawael; Indri Anugrahamadhani; Sahiruddhin Sahiruddhin (Jurnal Teknologi Informasi dan Pendidikan, 2026)
This study analyzes the quality of the Dukcapil (Department of Population and Civil Registration) website in South Sorong Regency, West Papua Province, using the Web Qual 4.0 method. The novelty of this study lies in its geographic focus on an underdeveloped eastern Indonesian region characterized by limited digital infrastructure and low digital literacy a context largely absent from existing e-government quality literature. A quantitative survey was conducted with 100 respondents selected through purposive sampling. The instrument demonstrated high reliability (Cronbach’s Alpha = 0.942 for performance; 0.928 for importance). Data were analyzed using descriptive statistics and Importance-Performance Analysis (IPA). Results indicate that all three Web Qual 4.0 dimensions scored below user expectations: usability (performance = 3.42; importance = 4.05), information quality (3.38; 4.24), and service interaction (3.35; 4.14), yielding an overall mean gap of -0.77. The below-average scores notably lower than comparable studies in urban areas such as Bandung (3.65) and Tangerang (3.58) reflect structural constraints including limited IT human resources, constrained budgets, and uneven internet infrastructure that are characteristic of eastern Indonesian regions rather than mere service quality deficiencies. IPA identified 9 priority attributes requiring immediate improvement, predominantly in information quality (e.g., information currency, gap = -1.30) and service interaction (e.g., data security, gap = -1.06; communication ease, gap = -1.00). This study recommends targeted improvements in content management, security systems, and interactive communication features, and calls for mixed-methods and comparative studies across eastern Indonesian regions to strengthen policy generalizability.